To kill a mockingbird - Pakula, Alan; Mulligan, Robert; Universal-International (Firm); Brentwood Productions, Inc. (Universal City, California : Universal Studio Home Entertainment, 2005)
Gregory Peck plays a southern lawyer who defends a black man accused of rape in this film version of the Pulitzer Prize-winning novel. The way in which it captures a time, a place, and above all, a mood, makes this film a masterpiece
disc 1. The film ; Bonus features: Academy Award best actor acceptance speech; American Film Institute Life Achievement Award; excerpt from Academy Tribute to Gregory Peck; Scout remembers; feature commentary with director Robert Mulligan and producer Alan Pakula; theatrical trailer - disc 2. A conversation with Gregory Peck / film by Cecilia Peck [et al.] ; produced & directed by Barbara Kopple (1999 ; 97 min.) ; Fearful symmetry: the making of To kill a mockingbird / a film by Charles Kiselyak. (1998 ; 90 min.)
Originally released as a motion picture in 1962
Screenplay, Horton Foote ; music, Elmer Bernstein
Cast : Gregory Pack, Robert Duvall, Mary Badham, Philip Alford, Rosemary Murphy, John Megna, Frank Overton, Brock Peters, Alice Ghostley, William Windom
Keywords: Race discrimination -- Drama; Racism -- Drama; Trials (Rape) -- Southern States -- Drama